2015
DOI: 10.1253/circj.cj-14-1013
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Role of Neural Arc in Sympathetic Baroreflex Resetting of Spontaneously Hypertensive Rats

Abstract: 592SATA Y et al. Circulation JournalOfficial Journal of the Japanese Circulation Society http://www. j-circ.or.jp classified as a short-term blood pressure control system, 8 carotid baroreflex activation therapy has succeeded in reducing blood pressure in patients with resistant hypertension for more than 1 year, 9 suggesting a potential role of the arterial baroreflex in the long-term regulation of blood pressure. 10 Considering the multifactorial and complex nature of hypertension, further research is needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
5
18
0
Order By: Relevance
“…3, C and D, Table 1), which is in agreement with our previous study (21). The two-way ANOVA did not show a significant effect of tempol on the slope or the intercept of the peripheral arc.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3, C and D, Table 1), which is in agreement with our previous study (21). The two-way ANOVA did not show a significant effect of tempol on the slope or the intercept of the peripheral arc.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the SNA value at the CSP level of 60 mmHg was assigned to 100% in individual animals. When SNA was rescaled on the basis of the pressor response to exogenous phenylephrine in our previous study (21), the response range of the neural arc became significantly greater in SHR than in WKY, and the slope of the peripheral arc did not differ between WKY and SHR. Although the rescaling of SNA affects the abscissa of the baroreflex equilibrium diagram, it does not affect the estimation of the operating-point AP because the ordinate is unchanged.…”
Section: Discussionmentioning
confidence: 81%
“…The reason for the relatively stronger nonlinearity in SHR 120 may pertain to the operating point. That is, the CSP levels for WKY and SHR 160 are in the linear regimes of their respective static sigmoidal CSP-AP relationships, while the CSP level for SHR 120 is near the nonlinear thresholding regime of its relationship (15). In this sense, comparisons between WKY and SHR 160 , as opposed to SHR 120 , may actually be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…9 Sata et al demonstrated that the neural arc of the carotid sinus baroreflex is upregulated, indicating that central sympathetic outflow is increased in SHR. 11 In contrast, the peripheral arc, which shows the function from SNA to the vessels, does not play a major role in determining AP in SHR. It should be noted, however, that baroreflex control of renal function needs to be evaluated if these data are to be applied to hypertension, considering the long-term AP control abnormality.…”
Section: Article P 592mentioning
confidence: 96%